Analisis Faktor–Faktor yang Mempengaruhi Brand Loyalty pada Coffee Shop yang ada di Batam: (Analysis of Factors Affecting Brand Loyalty at Coffee Shops in Batam) - Edy Yulianto Putra; Vina Liesty Indriani (UPT Penerbitan Universitas Jember, 2023)
This study aims to hide the factors that influence brand loyalty in coffee shops in Batam City by mediating brand image. The independent variables used in this study include trust, brand recommendations, perceived quality, lifestyle, and service quality. The methodology used in this study is a quantitative research methodology. Researchers used survey techniques through questionnaires to collect data. In this study, purposive sampling was applied, a sampling technique in which taking samples took into account certain criteria. The samples collected were 360 respondents. The data analysis method used is SEM (Structural Equation Modeling) with the help of SmartPLS 3 software.The results of this study found that trust, brand support, lifestyle, and service quality had a significant and positive effect on brand image, while perceived quality had no significant and positive effect on brand image. Meanwhile, brand image has a significant and positive effect on brand loyalty. The role of mediating brand image does not fully work as an intermediary. This is shown by the mediation of brand image does not have a significant and positive effect on the relationship of trust, brand recognition, perceived quality, and lifestyle with brand loyalty, while the relationship of service quality has a significant and positive effect on brand loyalty through brand image.